A systematic review of the educational uses and effects of exemplars. Issue 8 (14th November 2022) - To, Jessica; Panadero, Ernesto; Carless, David
Abstract: The analysis of exemplars of different quality is a potentially powerful tool in enabling students to understand assessment expectations and appreciate academic standards. Through a systematic review methodology, this paper synthesises exemplar-based research designs, exemplar implementation and the educational effects of exemplars. The review of 40 empirical exemplar-based studies indicated frequent use of post-intervention evaluation designs. The integrated use of exemplars and strategies such as rubrics, peer or self-assessment was a major pedagogic feature to enhance students' understanding of standards and aid their generation of internal feedback for self-monitoring. There was evidence suggesting that the combined use of exemplars with these strategies could advance students' academic performance and development of self-regulated learning. The review results set future directions for exemplar-based studies: quantitative research would benefit from controlled manipulation of variables to disentangle the effects of exemplars and those of other strategies; qualitative research could profitably use self-reflective diaries, think aloud protocols or classroom observations to develop deeper understandings of exemplar implementation. The key pedagogical implication recommends students' production of an assignment draft prior to exposure to exemplars so that they can compare their own work with exemplars and then make improvements independently of teachers.